Modified model reference adaptive control using lyapunov rule for power module in nuclear reactor system - Ghazali, Anith Khairunnisa (2017)
Reactor TRIGA PUSPATI (RTP) was successfully installed in 1982 at Malaysia Nuclear Agency and has been conducting safe operation for more than 35 years. It is the only research reactor in Malaysia. RTP is a TRIGA Mark II pool-type reactor, with 1 MW thermal power. The power system of the RTP was currently upgraded from relay mode to automated power control system. The safety features of the system also have been designed to avoid any abnormality in the electronic and associate components that may lead to uncontrolled rate of reactivity The reactivity and reactor power are controlled by the movements of four control rods, known as Safety, Shim, Regulating, and Transient. Currently, the RTP using PI controller indicates transient response with longer settling time and rise time. Thus, the efficiency of the reactor core is reduced and the reactor’s lifetime is shortened. Since the RTP is very important in various research fields, transient performance is vital. To overcome this problem, are quite challenging using PI controller since this controller are not capable to improve the transient response without produce overshoot and keep maintaining the steady state error less than 1% FP. Therefore, to solve this problem, it is necessary to design a controller that good in tracking and confirms the stability of the system. This research use Model Reference Adaptive Control MRAC controller to control the RTP power level because it good in adaptation and have a reference model. Even though the MRAC confirm the stability, but it gives unsatisfied performance to track the reference model. Thus, the modified (MRAC) with Lyapunov rule was proposed. The RTP model was modelled using a system identification method from its real-time power operation. Pole placement technique was applied to design the reference model with 47.8% ratio of movement. The stability of the proposed system was validated using transfer function test to ensure its capability. The Ziegler-Nichols technique was implemented to determine the adjustment mechanism. The adjustment mechanism will minimise the error of the reactor power to zero. The value of adjustment mechanism was determined by measuring the delay time and time constant from the operation data. The stability of controller has been checked using Lyapunov stability derivation. Results from the conventional MRAC and modified MRAC were compared and analysed. The percentage of improvement in terms of settling time was 33%, rise time was 33%, and there were no changes of for steady state error and tracking error. In conclusion, the modified MRAC had performed well in transient response, with settling time of 123.36 sec and rise time of 93.76 sec, which are applicable for a nuclear reactor power control system.